Determinan Nilai Perusahaan pada Emiten Sub-Sektor Plastik dan Kemasan di Indonesia: Peran Struktur Modal, Pertumbuhan Aset, dan Ukuran Perusahaan - Gusnafitri Gusnafitri (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze the effect of capital structure, asset growth, and firm size on firm value in plastic and packaging sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Firm value is proxied by Price to Book Value (PBV), capital structure is measured using the Debt to Equity Ratio (DER), asset growth is measured by the asset growth ratio, and firm size is measured using the natural logarithm of total assets. This research employed an explanatory quantitative approach using secondary data obtained from financial statements, annual reports, and stock price data. The sample consisted of 11 companies observed over five years, resulting in 55 panel data observations. Data were analyzed using panel data regression through the Common Effect Model, Fixed Effect Model, and Random Effect Model, with model selection based on the Chow, Hausman, and Lagrange Multiplier tests. The results indicate that capital structure, asset growth, and firm size have no significant effect on firm value, either partially or simultaneously. These findings suggest that firm value in the plastic and packaging sub-sector is not sufficiently explained by financing structure, asset expansion, or company size. Investors are more likely to consider other factors, such as profitability, operational efficiency, cash flow, sales growth, raw material risk, and sustainability prospects. Therefore, companies should improve financial performance, asset efficiency, cost control, and sustainable innovation to enhance firm value.